THE RELATIONSHIP BETWEEN ENVIRONMENTAL SANITATION AND THE INCIDENCE OF DENGUE HEMORRHAGIC FEVER (DBD) IN THE WORK AREA OF HOSPITAL X GRESIK SUB-DISTRICT - Nurfadila, Anisa; Mindiharto, Sestiono (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Dengue fever (DHF) is an infectious disease that is still a public health problem in Indonesia, including in Gresik District. Environmental factors, especially sanitation, have an important role in the spread of this disease. This study aims to determine the relationship between housing conditions, water reservoir conditions, and waste disposal systems with the incidence of DHF in the work area of Hospital X, Gresik District in 2025. This study used a quantitative analytic approach with a cross sectional design. The number of respondents was 106 people selected using random sampling technique. Data collection was done through questionnaires and observation, then analyzed using the chi-square test. The results showed that there was a significant relationship between house condition (p = 0.014), water reservoir condition (p = 0.031), and waste disposal system (p = 0.021) with DHF incidence. The conclusion of this study is that environmental sanitation has a significant relationship with the incidence of DHF, so it is necessary to improve sanitation as a preventive measure in the community.